Exchange Rate Fluctuations and the Performance of Nairobi Securities Exchange Market in Kenya During the Coronavirus Pandemic - Koskei, Loice (International Journal of Business, Economics and Management, 2020)
The global financial and economic shocks which were triggered by the Coronavirus pandemic prompted a market halt causing a major spark in the Nairobi Securities exchange that resulted in panic selling. The Corona virus pandemic led to volatility of exchange rates causing a sharp depreciation of the shilling which further affected the performance of the securities market. The study investigated the effect of exchange rate fluctuations on the performance of the Nairobi securities exchange for the 5 months period of the year 2020. Daily time series data collected from Nairobi Securities exchange, Central bank of Kenya and Kenya National Bureau of Statistics for the period January to May 2020 was used. The multiple regression model results pointed out that exchange rate fluctuation had a negative and statistically insignificant effect on the performance of Nairobi securities exchange in Kenya during the Coronavirus period. The results implied that exchange rate fluctuations do not affect the performance of Nairobi securities exchange market in Kenya as measured by NASI. Inflation rate results had a positive and statistically significant effect with NASI. The results implied that inflation rate affect the performance of Nairobi securities exchange market as measured by NASI. 91-day treasury bills rate had negative but statistically significant effect on NASI implying that a decrease in 91- day Treasury bill rate enhances the performance of Nairobi securities exchange as measured by NASI. Investors need to be conscious of the macroeconomic variables that influence the security prices particularly during pandemics like the Coronavirus.